Assessment of Mothers Knowledge and Practices with Hemophilic Children type A at Azadi Teaching Hospital in Kirkuk City - mohammed, Aram; hattab, Khatam (Iraqi National Journal of Nursing Specialties, 2013)
Objective: The study aims to assess the knowledge and practices of mothers with hemophilia children type - A - , socio-economic status and association between mother demographic information with their knowledge and practices toward their children in Azadi Teaching Hospital in Kirkuk. Methodology: Descriptive study no probability (purposive) sample. Selected Fifty-five of mothers having hemophilia children, started from November 2012 to May 2013. Study was carried out in the Azadi teaching hospital in Kirkuk. By using questionnaire which consists from five parts include demographic characteristics for mother and children, socio-economic, Knowledge and practices data gathered, by direct interview with the mothers in the hospital. Reliability and content validity of questioner were identified form of the pilot study. Descriptive and inferential statistical used to analysis of data. Results: The results of the study (30.9%) of the mothers were aged (40 - 44) and (43.6%) were graduates from primary school. And their hemophilia children in all sample sex male, (41.8%) of hemophilia children were aged between (5-9) years though (30.9 %) are not in school and that (69.1%) of the families have one child hemophilia infected and (27.6%) were diagnosis bleeding in joint , level of severity of the disease (65.5%) was moderate ,(98.2%) of family depended on hospital to provide factor eight and other treatment to hemophilia child when bleeding. socio – economic status of family show ( 61.8%) low status. (83.6%) of mothers uncertain of their information about hemophilia, mother practices were (72.7%) sometimes and (23.6%) never done good practice to their hemophilia children. Recommendations: Develop special booklet for mothers local languages (Kurdish , Turkish ) develop programs and awareness courses (theoretical and practical) for mothers and support family financial improve and provide factor eighth for hospitals and health center where patients found.